'Women take care and men take charge': The case of leadership and gender in the Public and Commercial Services Union. (May 2022) - Prowse, Julie; Prowse, Peter; Perrett, Robert
This article presents the findings of a case study that aimed to understand the specific leadership styles that are valued by women and men lay representatives in the Public and Commercial Services Union (PCS) and to determine the gendered implications for increasing women's leadership and representation in trade unions. Survey responses from PCS lay representatives (reps) show the majority of women and men agreed that the leadership style they value, and that makes a good union leader, is post-heroic (communal) leadership. This approach is associated with leadership characteristics such as being helpful, sensitive and kind and are generally practised by women. This contrasts with male union leaders who are associated with a traditional, heroic (agentic) leadership style characterised by confidence, self-reliance and decisiveness. Although some differences exist that highlight gender issues, both women and men lay reps have positive attitudes towards increasing women's representation and participation in union leadership.